Contribution of Agroforestry Plants to Farmers' Income and Welfare - Wanderi, Wanderi; Qurniati, Rommy; Kaskoyo, Hari (Department of Forestry, Faculty of Agriculture, University of Lampung, 2019)
The people who live adjacent to Tahura Wan Abdul Rachman depend their lives on land management in the block utilization of Tahura with the agroforestry system. This system is implemented with different plant compositions so that the effect on income is different. This study aims to determine the composition of agroforestry plants that provide the highest income and welfare level for farmers. The study was conducted in 2017 in Sidodadi Village, Pesawaran District, which borders Tahura Wan Abdul Rahman. The variables analyzed consisted of revenue and production costs in the management of agroforestry, farmer expenditure and the number of family member. The results obtained from the 7 plant compositions identified, composition II with the main plants of banana and cacao and other types of plants are clove, chili, areca nut, soursop, mango, rambutan, durian, coconut, pecan, duku, jengkol, petai, avocado, nutmeg , breadfruit, sugar palm, bayur and cempaka; provide the highest income with an average income of Rp. 21,640,777/family/year but this income is still in a sufficient category and is only limited to meeting basic needs. It is the composition of plants that are most widely used by the community. Keywords: agroforestry, income, plant composition, welfare